2017
DOI: 10.1016/j.eswa.2017.01.045
|View full text |Cite
|
Sign up to set email alerts
|

Make it personal: A social explanation system applied to group recommendations

Abstract: Recommender systems help users to identify which items from a variety of choices best match their needs and preferences. In this context, explanations act as complementary information that can help users to better comprehend the system's output and to encourage goals such as trust, confidence in decision-making or utility. In this paper we propose a Personalized Social Individual Explanation approach (PS IE). Unlike other expert systems the PS IE proposal novelly includes explanations about the system's group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…In this framework, a recommendation can be explained based on the target user's friends who have similar preferences, as shown in Figure 2.12. Quijano-Sanchez et al (2017) introduced a social explanation system applied to group recommendation, which significantly increased the likelihood of the user acceptance, the user satisfaction, and the system efficiency to help users make decisions. Wang et al (2014) generates social explanations such as "A and B also like the item".…”
Section: Social Explanationmentioning
confidence: 99%
“…In this framework, a recommendation can be explained based on the target user's friends who have similar preferences, as shown in Figure 2.12. Quijano-Sanchez et al (2017) introduced a social explanation system applied to group recommendation, which significantly increased the likelihood of the user acceptance, the user satisfaction, and the system efficiency to help users make decisions. Wang et al (2014) generates social explanations such as "A and B also like the item".…”
Section: Social Explanationmentioning
confidence: 99%
“…To get the best recommendation which matches the user request, the users and the providers must cooperate. In [67] propose a Personalized Social Individual Explanation approach ( PSIE ) Which led to improve trustworthiness and users' satisfaction • Gray-Sheep: When the user opinion is not clear or cannot be classified correctly, it is known as gray sheep information which means uncertain value. It's lead to a lack of benefit from this information.…”
Section: B Limitations Of Recommendation Systemmentioning
confidence: 99%
“…GR is an important application problem in many social activities and industries, such as online shopping, music sharing and group travelling. GR belongs to social services [10], so it inevitably emphasizes the service quality (QoS) [11], and privacy preservation and dynamicity [12]. Service recommendation research has a long history, along with personalized recommendation technology, such as collaborative filtering (CF) [13], matrix decomposition (MF) [14] and deep learning (DL) [15] have been widely studied and the research on group recommendation is still very limited.…”
Section: Group Recommendationmentioning
confidence: 99%
“…Alistair et al [21] conducted relevant research on the role of SBH online and offline social activities in social relationships, and the experiment showed that the satisfaction of group members in social activities increased with the increase in intimacy. Lara Quijano-Sanchez et al [10] gave comprehensive consideration to the satisfaction of the group and the friendly relationship within the group and put forward a personalized group recommendation method (personalized social individual explanation). Yue Ding et al [22] calculated the influence value of users through the social interaction information of users in the group and the similarity relationship between users and then used the regularization classification method to deal with the problem of different preferences among users in the group.…”
Section: Social Recommendationmentioning
confidence: 99%